Preventing childhood unintentional injuries–what works? A literature review. Issue 2 (June 1996) - Dowswell, T.; Towner, E. M.; Simpson, G.; Jarvis, S. N.
Abstract : AIM: The aim of this paper is to report on a systematic review of the world literature to provide information about the most effective forms of health promotion interventions to reduce childhood (0-14 years) unintentional injuries. The findings are of relevance to policy makers at a local or national level, to practitioners and researchers. METHODS: The relevant literature has been identified through the use of electronic databases, hand searching of journals, scanning reference lists, and consultation with key informants. RESULTS: Examples of interventions that have been effective in reducing injury include: bicycle helmet legislation, area wide traffic calming measures, child safety restraint legislation, child resistant containers to prevent poisoning, and window bars to prevent falls. Interventions effective in changing behaviour include bicycle helmet education and legislation, child restraint legislation, child restraint loan schemes, child restraint educational campaigns, pedestrian education aimed at the child/parent, provision of smoke detectors, and parent education on home hazard reduction. For the community based campaigns, the key to success has been the sustained use of surveillance systems, the commitment of interagency cooperation and the time needed to develop networks and implement a range of interventions. Education, environmental modification and legislation all have a part to play and their effect in combination is important. CONCLUSION: The design of evaluations in injury prevention needs to be improved so that more reliable evidence can be obtained. Better information is needed on process, so that successful strategies can be replicated elsewhere. There is also a need for literature reviews on effectiveness to be updated regularly and for their findings to be widely disseminated to policy makers, researchers, and practitioners.